Effects of low plastic burnishing combined with self-oxygen diffusion on the hot corrosion behavior of the TA29 titanium alloy - Congjie Kang; Hongyun Luo; Jianming Cai; Duoqi Shi (Journal of Materials Research and Technology)
The paper investigates the hot corrosion behavior of three types of specimens of TA29 Ti alloy after solution aging treatment (SAT), low plastic burnishing (LPB) and LPB combined with self-oxygen diffusion (LPB-OD) at 600 °C. The results show that the surface grains of LPB specimens were refined and produced a large number of dislocations, stacking faults, grain boundaries and subgrain boundaries. This is conducive to the diffusion of Al element in the matrix to the surface of the matrix during the hot corrosion process to form a continuous and dense Al2O3 protective layer to improve the hot corrosion resistance of the specimen. The LPB-OD specimen undergoes self-oxygen diffusion processing to obtain an O rich surface layer and promote the enrichment of Al element with strong affinity for oxygen towards the surface of the specimen, resulting in the formation of a special double-layer Al rich oxide layer during the hot corrosion. This special protective layer further improves the hot corrosion resistance of LPB-OD specimen. This paper discusses the mechanism of the hot corrosion process of TA29 Ti alloy and reveals the mechanism of the formation of a special double-layer Al rich oxide layer under the combined influence of metal element cyclic chlorination oxidation and surface Al element enrichment caused by self-oxygen diffusion processing, which provides a new way of thinking to improve the hot corrosion performance of Ti alloy.